Digital Parenting Education: Today's Parenting as a Form of Digital Disaster Mitigation - Sumi Lestari; Intan Rahmawati; Dewi Puri Astiti; Khoirul Anam (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2025)
Parents in the digital era are in a complex position they are expected to possess knowledge and adapt to rapid technological advancements while still fulfilling their primary role of educating and guiding their children. In reality, there is a significant digital gap between generations in society. Digital parenting education is an appropriate solution to bridge the gap between the younger and older generations. Through digital parenting education, parents gain knowledge, skills, an understanding of the benefits and risks of digital usage, as well as parenting strategies that align with technological and informational developments in the digital age. This serves as an effort to mitigate digital disasters affecting children. The goal of this outreach program for parents is to provide education on digital parenting literacy so that parents can improve the quality of communication patterns within the family and reduce the risk of excessive gadget use among children. This is achieved by encouraging parents to implement gadget-use agreements through two-way communication. The method used in this community service activity was educational outreach to members of Fatayat NU Landungsari branch. The activity was attended by around 45 members of Fatayat NU from the Landungsari branch, who also served as partners in this initiative. The results of the activity, based on post-tests and interviews, indicated that the mothers gained new knowledge about the importance of supervising children’s gadget use. They also developed an understanding of the negative impacts of uncontrolled gadget use, ranging from academic consequences to the child’s psychological and emotional condition. The participants committed to engaging in two-way communication with their children so that the children can learn to use gadgets wisely and appropriately.Orang tua di era digital berada pada posisi yang kompleks, mereka dituntut untuk memiliki pengetahuan dan beradaptasi terhadap perkembangan teknologi yang secara cepat sembari mereka tetap wajib menjalankan peran primer mereka dalam mendidik dan mengarahkan anak-anak mereka. Kenyataannya bahwa di masyarakat terjadi kesenjangan digital antar generasi yang sangat signifikan, edukasi parenting digital merupakan solusi yang tepat dalam menjembatani kesenjangan yang terjadi antara generasi anak dan orang tua. Melalui edukasi parenting digital orang tua memperoleh pengetahuan, keterampilan, manfaat dan risiko penggunaan digital serta strategi pengasuhan yang sesuai dengan perkembangan teknologi dan informasi di era digital, hal ini sebagai upaya mitigasi bencana digital pada anak. Tujuan penyuluhan kepada orang tua adalah untuk memberikan edukasi tentang literasi digital parenting, agar orang tua mampu memperbaiki kualitas pola komunikasi dalam keluarga dan menurunkan resiko perilaku penggunaan gadget yang berlebihan pada anak karena orang tua berupaya menerapkan perjanjian penggunaan gadget dengan komunikasi dua arah. Metode kegiatan pengabdian masyarakat ini adalah dengan menggunakan penyuluhan kepada ibu-ibu Fatayat NU cabang Landungsari, kegiatan ini diikuti sekitar 45 ibu-ibu Fatayat NU cabang Landungsari, mitra dalam kegiatan ini adalah Fatayat NU cabang Landungsari. Hasil kegiatan ini berdasarkan pada post test dan wawancara adalah bahwa ibu-ibu memiliki pengetahuan baru tentang pentingnya pendampingan penggunaan gadget pada anak, memahami dampak negatif ketika anak tidak dikontrol dalam penggunaan gadget dari dampak akademis hingga kondisi psikologis atau emosi anak, peserta berkomitmen untuk melakukan komunikasi dua arah dengan anak agar mereka mampu menggunakan gadget secara bijak dan sesuai kebutuhan.